Analysis of clinico-sonological parameters of women with preterm pregnancy with complaint of lower abdominal pain - Maheshwari, Raghavi; Verma, Aruna; Gupta, Abhilasha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical length and dilatation are important parameters to be evaluated for the diagnosis of threatened preterm labor, and they may have an important role in the risk stratification of women presenting with preterm labor. Thus, the study was planned to analyse clinicosonological parameters in women with preterm pregnancy who came with complaint of lower abdominal pain. Methods: A total of 200 pregnant women with 28 to 35±6 weeks of gestation admitted with pain abdomen underwent complete history and examination, followed by relevant antenatal investigations. Transvaginal ultrasonic CL and dilatation measurement at the time of admission and after 4-6 hours of observation were done. The subjects were followed and admission-delivery interval was noted. Statistical analysis was done by applying the appropriate Chi-square test for the comparison of proportions. Results: Four percent of patients had a cervical length <2 cm at admission, 40% had a cervical length between 2-3 cm and 56% of patients had a cervical length ≥3 cm. The difference between the 3 groups was statistically significant (p value <0.000001) and 100% of patients with cervical length <2 cm were delivered within one week. Fifteen percent of patients had changes in cervical length after 4-6 hours of observation and 85% did not have any change in cervical length. The difference was statistically significant (p value <0.0000001). Conclusions: Cervical length and dilatation measurement by transvaginal sonography (TVS) has a positive correlation with the admission to the delivery interval.